Evolution of Malaysia’s Plans Policies, Initiatives and Strategies on Green Procurement Implementation: A Review - Bidin, Zafikha Aida; Mohamad Bohari , Asmah Alia; Hashim , Norfashiha; Zanudin, Khalid; Lestari (International Journal of Sustainable Construction Engineering and Technology, 2023)
Malaysia’s plans have evolved over the years, highlighting several goals to sustain economic growth and development in all constituent states of Malaysia. The five-year development plan comprises a comprehensive and integrated plan, policies, and strategies to lead the government in achieving the desired economic and socioeconomic goals. The first Malaysia plan was introduced in 1966-1970, and the development of Malaysia’s plans has continued since then. In the Tenth Malaysia Plan, the government emphasised sustainable management, responding to global climate change, and focusing on strategies and mitigation adaptation to ensure sustainable growth. Keeping environmental sustainability is a global commitment, especially in the construction industry, which contributes the most to environmental issues. Green procurement has been introduced to the construction industry as a way forward and a strategy towards sustainability. The primary objective of this paper is to analyse the evolution of the five-year development plans policies, initiatives, and strategies that have been proposed by the government on green procurement practices in Malaysia’s plans. The study employs integrative literature review to analyse the contents and features of Malaysia’s plans and its related government policy documents on green procurement. The findings of this study will assist stakeholders in better understanding the significance of green policies, initiatives, and strategies on green procurement implementation in Malaysia’s plans towards achieving inclusive, sustainable development in the construction industry.